2014
DOI: 10.3329/icpj.v3i10.20337
|View full text |Cite
|
Sign up to set email alerts
|

Potential antibacterial activity of crude extracts and silver nanoparticles synthesized from Sargassum wightii

Abstract: The present work investigates the antibacterial activity of silver nanoparticles (Ag-NPs) synthesized by biological method using Sargassum wightii. The fresh live seaweed was collected from the Mandapam coast of Tamilnadu, India. Solvent extract was prepared using acetone, petroleum ether and methanol. Aqueous extract of the seaweed was also used for the synthesis of silver Ag-NPs. Seaweed extract is used as a reducing agent of 2mM silver nitrate solution for the synthesis of Ag-NPs. Periodical monitoring of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 10 publications
0
3
1
Order By: Relevance
“…In our results, ZOI formed by S. wightii methanol extracts against S. aureus was the highest, which was 2.9-fold higher than previously observed for S. wightii methanol extract from Mandapam [31] and agreed that methanol extract for S. wightii against S. aureus was better than other solvents [42]. Though, S. wightii butanol and ethyl acetate extracts showed considerable bioactivity against both S. aureus, P. aeruginosa and E. coli in our results, S. wightii methanol extracts showed no bioactivity against E. coli, which agreed with the findings for Sargassum vulgare with no activity [44] and disagreed with observations for S. wightii [45].…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…In our results, ZOI formed by S. wightii methanol extracts against S. aureus was the highest, which was 2.9-fold higher than previously observed for S. wightii methanol extract from Mandapam [31] and agreed that methanol extract for S. wightii against S. aureus was better than other solvents [42]. Though, S. wightii butanol and ethyl acetate extracts showed considerable bioactivity against both S. aureus, P. aeruginosa and E. coli in our results, S. wightii methanol extracts showed no bioactivity against E. coli, which agreed with the findings for Sargassum vulgare with no activity [44] and disagreed with observations for S. wightii [45].…”
Section: Discussioncontrasting
confidence: 65%
“…However, methanol extracts of both U. reticulata and U. lactuca were effective against human pathogens [30]. In case of Sargassum wightii methanol extracts were effective against S. aureus [31] and against E. coli, and P. aeruginosa [32], whereas ethyl acetate extracts of S. wightii were only effective against Bacillus subtilis [33].…”
Section: Introductionmentioning
confidence: 99%
“…Comparing the results of the present study with silver and gold nanoparticles produced with extracts of the brown seaweeds Cystoseira tamariscifolia and Cystoseira baccata, the MIC values for the non-biofilm-producing bacteria are at much lower concentrations with the biogenic U. pinnatifida nanoparticles [48]. Other authors reported that silver nanoparticles synthesized in Sargassum wightii (average size 48.78 nm) were toxic to S. aureus at a MIC of 130 µg/mL [49], while particles produced in Turbinaria conoides (up to 80 nm) showed a MIC of 64 and 8 µg/mL against P. aeruginosa and S. aureus, respectively [50]. Gold nanoparticles produced in Sargassum illicifolium (20-25 nm) and in Sargassum muticum (10.4 ± 1.2 nm) registered a MIC in planktonic S. aureus of 48 and 39.5 µg/mL, respectively [42,51].…”
Section: Antibacterial Activity Of Up Extract Ag@up and Au@upmentioning
confidence: 48%
“…Research aiming to combine 3DLL and biomedicine is currently gathering a great deal of interest and shows promising results in creating 3D scaffolds for stem cell growth [21,42]. It was shown that nanoparticles in general can perform many different roles in medicine, such as antibacterial agents [54], helping with magnetic fluid hyperthermia [55] or use for advanced drug or even gene delivery [56]. The inclusion of nanoparticles in polymer structures can lead to active medical implants that have desired properties and biofunctionalisation given by the nanoparticles or even act as a nanoparticle delivery system if the polymer is biodegradable [57].…”
Section: Discussionmentioning
confidence: 99%